Jacques Rancière : an introduction - Tanke, Joseph J. (London ; New York : Continuum, 2011)
1. For A Critique of Philosophy##Introduction##1.1. The Lesson of Althusser##1.2. The Lessons of May##1.3. Lessons From the Archives##1.4. Lessons on Philosopher-Kings##1.5. Lessons From Equality##Conclusion## ##2. Politics By Process of Elimination##Introduction##2.1. On the Terrain of Policed Consensus##2.2. The Aesthetics of Counting##2.3. Supposing, Verifying, and Demonstrating Equality##2.4. Disputing Subjects and Litigious Objects: Politics as Dissensus##2.5. The Subjective Process of Politics##Conclusion## ##3. Retrieving the Politics of Aesthetics##Introduction##3.1. Analyzing the Part of Art##3.2. Three Regimes of Art##3.3. Equality in Art##3.4. In Place of Modernity##3.5. Against Postmodernity##3.6. Art as Dissensus##Conclusion## ##4. Regimes of Cinema##Introduction##4.1. A Historical Poetics of Cinema##4.2. Cinema, the Dream of the Aesthetic Age##4.3. The Logic of the Thwarted Fable##4.4. Allegories of Modernity: Deleuze and the Use of Hitchcock##4.5. Cinema and Its Century: Godard and the Abuse of Hitchcock##Conclusion## ##5. Beyond Ranciere##Introduction##5.1. Sensing Equality?##5.2. The Centrality of the Imagination##5.3. Inventing the Trans-Subjective Imagination
Includes bibliographical references and index.
boek
Keywords: Rancière, Jacques